2007
DOI: 10.1189/jlb.0607349
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia transcriptionally induces macrophage-inflammatory protein-3α/CCL-20 in primary human mononuclear phagocytes through nuclear factor (NF)-κB

Abstract: Hypoxia, a condition of low oxygen tension, occurring in many pathological processes, modifies the mononuclear phagocyte transcriptional profile. Here, we demonstrate hypoxic up-regulation of the CCL20 chemokine in primary human monocytes (Mn) and macrophages. mRNA induction was paralleled by protein secretion and dependent on gene transcription activation. Functional studies of the CCL20 promoter using a series of 5'-deleted and mutated reporter constructs demonstrated the requirement for the NF-kappaB-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…It is noteworthy that NF-B has also been involved in the modulation of CCL20 by other mediators such as TNF␣ in a human cancer cell line, 38 prolactin in keratinocytes, 35 or hypoxia in primary human monocytes/ macrophages. 39 Taken together these results emphasize the role of NF-B in the modulation of CCL20 by lipoproteins and other inducers. Concerning the mechanism involved in such effect, lipoprotein receptors do not seem to play a major role.…”
Section: Discussionmentioning
confidence: 62%
“…It is noteworthy that NF-B has also been involved in the modulation of CCL20 by other mediators such as TNF␣ in a human cancer cell line, 38 prolactin in keratinocytes, 35 or hypoxia in primary human monocytes/ macrophages. 39 Taken together these results emphasize the role of NF-B in the modulation of CCL20 by lipoproteins and other inducers. Concerning the mechanism involved in such effect, lipoprotein receptors do not seem to play a major role.…”
Section: Discussionmentioning
confidence: 62%
“…Increased p50 levels do not appear to mediate Notch induction of NF-kB activity in Raw cells (Fig. 5D), but we cannot rule out that this could arrive in particular promoter contexts, as the role of p50 depends largely on that [29,31]. NF-kB p65 levels seem to be less affected by Notch1 signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Although p50 homodimers have been classically considered as transcriptional inhibitory proteins, recent works have shown that in some promoter contexts they are able to increase NF-kBdependent transcription [29,31]. To evaluate whether Notch1 could modify p50 transcriptional activity, we transfected increasing amounts of a p50 expression vector and an NF-kBluciferase reporter construct in Raw-NIC or Raw control cells.…”
Section: Mechanism Of Notch-nf-jb Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Although dendritic cells accumulate HIF-1␣ in hypoxia, 39 immature forms of this cell type up-regulate other hypoxiaresponsive genes, such as CCL20 via up-regulated p50/p50 NF-B homodimers rather than HIFs. 40 A study of the responses of such related myeloid cell types to identical hypoxic conditions would be interesting but beyond the remit of this study.…”
Section: Discussionmentioning
confidence: 99%